Peningkatan Pengetahuan Siswa Panti Asuhan Bina Putra Tentang Vaksinasi - Marius Agung Sasmita Jati; Eva Runi Khristiani; Muryani (J.Abdimas: Community Health, 2022)
Knowledge about vaccination is rarely obtained at every level of school, this causes students' knowledge about vaccination, especially COVID-19, to be lacking. This requires attention and the community service program that is carried out is an information delivery program and is useful for increasing knowledge about vaccination, especially COVID-19. The program carried out is to increase knowledge about vaccination for students at the Bina Putra Bantul Orphanage, Yogyakarta. Delivery of information about the benefits of vaccination is currently experiencing a decline resulting in ignorance among a group of people. Activities that have been carried out are counseling programs with face-to-face lectures. Submission of material is done with the help of a presentation screen and a video. The results of the activities that have been carried out are an increase in knowledge, as measured by tools in the form of pretest and posttest questionnaires; the result is that the percentage of students who answered the questions correctly increased by 54% (correct score <10), 58% (10≤correct score≤15), and 93% (correct score>15). Participants who took part in this program were 37 students. This extension program was concluded to be able to increase knowledge about vaccination in groups of students at the SMK level. Keywords: Knowledge, Vaccination, Counseling